2013
DOI: 10.1073/pnas.1219283110
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the plankton paleome in the Black Sea from the Deglacial to Anthropocene

Abstract: The complex interplay of climate shifts over Eurasia and global sea level changes modulates freshwater and saltwater inputs to the Black Sea. The dynamics of the hydrologic changes from the Late Glacial into the Holocene remain a matter of debate, and information on how these changes affected the ecology of the Black Sea is sparse. Here we used Roche 454 next-generation pyrosequencing of sedimentary 18S rRNA genes to reconstruct the plankton community structure in the Black Sea over the last ca. 11,400 y. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
164
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 47 publications
12
164
1
Order By: Relevance
“…The diversity of microbial life will be quantified and compared with geological and geochemical data to answer questions such as was the microbiology shaped by the post-impact hydrothermal system, and did organic matter get trapped within hydrothermal minerals? The deep biosphere will be investigated using culturing, molecular biological analyses of DNA, searching for biosignatures such as hopanoids and other lipids/biomolecules, and paired analyses of paleome (the genome of an extinct species) and lipid biomarkers (Cockell et al, 2005;Coolen and Overmann, 2007;Coolen et al, 2013). Iron isotopes will also be used to detect biosignatures because they are particularly useful for studies of ancient, severely metamorphosed and/or altered rocks (Yamaguchi et al, 2005).…”
Section: Deep Biosphere and Habitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The diversity of microbial life will be quantified and compared with geological and geochemical data to answer questions such as was the microbiology shaped by the post-impact hydrothermal system, and did organic matter get trapped within hydrothermal minerals? The deep biosphere will be investigated using culturing, molecular biological analyses of DNA, searching for biosignatures such as hopanoids and other lipids/biomolecules, and paired analyses of paleome (the genome of an extinct species) and lipid biomarkers (Cockell et al, 2005;Coolen and Overmann, 2007;Coolen et al, 2013). Iron isotopes will also be used to detect biosignatures because they are particularly useful for studies of ancient, severely metamorphosed and/or altered rocks (Yamaguchi et al, 2005).…”
Section: Deep Biosphere and Habitabilitymentioning
confidence: 99%
“…Study of biomarkers at the molecular level (high-pressure liquid chromatography [HPLC] and liquid chromatography-mass spectrometry [LC-MS]) and pigments (chlorophylls, bacteriochlorophylls, and their degradation products) from photosynthetic organisms (algae and photosynthetic bacteria) may indicate changes in and evolution of photosynthetic organism populations after impact. It is expected that both marine and terrestrial organic matter have accumulated in the post-impact sedimentary rock and that the paired stratigraphic analysis of the paleome and lipid biomarkers and their isotopic compositions using precisely dated core material will provide detailed insights into post-impact environmental conditions and the recovery and evolution of surface and deep subsurface life (Coolen et al, 2007(Coolen et al, , 2013. Of interest is the ocean chemistry and temperature immediately following the impact and any indicators of climatic recovery.…”
Section: Recovery Of Lifementioning
confidence: 99%
“…In marine sediments, the presence of eDNA sequences has been reported from organic-rich layers in the Mediterranean dating back to 217 ka (Coolen and Overmann, 2007) and 125 ka (Boere et al, 2011), in sediments covering the last 11.4 kyr in the Black Sea (Coolen et al, 2013), and in up to 32.5 kyr old deposits in the Atlantic (Lejzerowicz et al, 2013;Pawłowska et al, 2014). Recently, Kirkpatrick et al (2016) showed that the abundance of planktonic DNA was decreasing within 100-200 ka in sediments of the Bering Sea but traces were still detected in sediments up to 1.4 Ma.…”
Section: Introductionmentioning
confidence: 99%
“…These two effects act in concert so that alkenone δD becomes less negative as salinity increases. As such, the δD of alkenones recovered from sediment cores has been used to estimate changes in past surface salinity, for example, in the Eastern Mediterranean (van der Meer et al, 2007), the Black Sea (van der Meer et al, 2008;Coolen et al, 2013) and the Agulhas region (Kasper et al, 2014).The reason for this correlation between salinity and fractionation is presently not clear. One hypothesis for the increase in fractionation factor observed with increasing salinity is that at higher salinities water transport across cell membranes is reduced as the cell maintains osmotic potential and that this reduced transport decreases the effective size of the pool of internal cell water from which hydrogen can be fixed (Sachse and Sachs, 2008).…”
mentioning
confidence: 99%